2018
DOI: 10.3389/fcimb.2018.00081
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NLRP3 Inflammasome Pathway by Uropathogenic Escherichia coli Is Virulence Factor-Dependent and Influences Colonization of Bladder Epithelial Cells

Abstract: The NLRP3 inflammasome and IL-1β release have recently been suggested to be important for the progression of urinary tract infection (UTI). However, much is still unknown regarding the interaction of UPEC and the NLRP3 inflammasome. The purpose of this study was to elucidate what virulence factors uropathogenic Escherichia coli (UPEC) use to modulate NLRP3 inflammasome activation and subsequent IL-1β release and the role of NLRP3 for UPEC colonization of bladder epithelial cells. The bladder epithelial cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 66 publications
4
81
0
Order By: Relevance
“…interactions in Bladder Epithelial Cells (Demirel et al, 2018) and BMECs (Li et al, 2019). In the present study, we found that NLRP3 gene was upregulated at both transcript and protein levels, and knockdown of NLRP3 expression inhibited the expression of pro-caspase-1, IL-1β, and PTGS (COX-2).…”
supporting
confidence: 51%
“…interactions in Bladder Epithelial Cells (Demirel et al, 2018) and BMECs (Li et al, 2019). In the present study, we found that NLRP3 gene was upregulated at both transcript and protein levels, and knockdown of NLRP3 expression inhibited the expression of pro-caspase-1, IL-1β, and PTGS (COX-2).…”
supporting
confidence: 51%
“…Conversely, pathogenic bacteria -specifically uropathogenic E. coli (UPEC) -can stimulate the inflammasome in urothelial cells, whereas non-pathogenic strains of E. coli do not. [52] Taken together, these data suggest that the response of host tissue to specific bacteria within the microbiome may modulate cancerassociated inflammation. Indeed, dysregulation of the extracellular matrix (ECM), which can occur as a result of age or a variety of diseases, plays a critical role in tumorigenesis through generation of a tumorigenic environment, including facilitation of angiogenesis and inflammation.…”
Section: Discussionmentioning
confidence: 85%
“…After the UPEC bacteria with MOI=20 stimulated the J774A.1 and Raw264.7 macrophage cell lines for 2 h, the cells were treated with the NPS2143 inhibitor for 4 h. According to the manufacturer's instructions, cell viability was assessed by Pierce LDH cytotoxicity assay (Beyotime, China) and neutral red toxicity assay (Beyotime, China) (17).…”
Section: Cell Viability Measurementsmentioning
confidence: 99%